Serum Levels of Interleukin-1 Alpha and Interleukin-6 in Acute Coronary Syndrome Patients (Iraqi Journal of Medical Sciences, 2016)
Background:Cytokines are responsible for the modulation of immunological and inflammatory processes and play a significant role in the pathogenesis of acute coronary syndrome patients (ACS).Objective:This study aims to investigate the serum levels of IL-1? and IL-6 in ACS patients.Methods: The study covered 140 subjects. It comprised a total of 101 patients with ACS patients [62 with acute myocardial infarction (AMI) and 39 with unstable angina (UA)], compared with 39 healthy individuals with no history of cardiac disease. Serum IL-1? and IL-6 analysis was performed by ELISA.Results:The present results revealed that there were significant elevation in mean serum levels of IL-1? and IL-6 in patients with ACS ( AMI and UA) as compared to healthy control (P
Keywords: Acute coronary syndrome; IL1 and IL6